The Impact of ESG (Environmental, Social, Governance) Initiatives on Investment Decisions in the Indonesian Capital Market - Kholida, Nikmah; Hapsari, Lin; Hikmah, I'in Nurul (Jurnal Ilmiah Manajemen, Ekonomi dan Bisnis, 2025)
n recent years, Environmental, Social, and Governance (ESG) initiatives have sprouted into the front and center of both the global and national investment stage. In Indonesia, while the regulators and corporations have made their attempt in the promotion of ESG practices, how much such practices are construed to be influential in investment decisions remains ambiguous. Therefore, this study aims at providing an empirical study of the impact of ESG initiatives on investment decisions in the Indonesian capital market, evaluate which ESG dimension is most influential, and look at the mediating role of investor perception. This study adopts a quantitative explanatory approach, using Structural Equation Modeling based on Partial Least Squares (SEM-PLS), with an estimation of 135 firms' ESG data along with the perceptions of 200 investors. The findings indicate that ESG initiatives exert a significant influence on investment decisions, and governance is the most prominent factor. Moreover, it was found that investor perception has a considerable mediating role in the relationship between ESG and investment decisions. This study thus offers a new approach to the literature on ESG in Indonesia, as it integrates and contextualizes the results while emphasizing the key role of investor perception in sustainable investment decision-making.